Incidence of vitamin D deficiency in adolescent idiopathic scoliosis: a meta-analysis - Llopis-Ibor, Clara Inés; Mariscal, Gonzalo; de la Rubia Ortí, Jose Enrique; Barrios, Carlos (Frontiers in Endocrinology, 2023)
This study aimed to investigate the incidence of vitamin D deficiency in patients with adolescent idiopathic scoliosis through a meta-analysis and to analyze trends and risk factors. Potentially relevant studies were searched using the terms "Vitamin D AND scoliosis." Data on the incidence and risk factors, such as race, curve magnitude, and sex, were extracted from the selected studies. Review Manager 5.4 software was used for the data analysis. Six studies with a total of 1, 428 patients met the inclusion criteria. The incidence of vitamin D insufficiency in patients with idiopathic scoliosis was 36.19% (95% CI [21.93 to 50.46]. In contrast, the incidence of vitamin D deficiency was 41.43% (95% CI [16.62 66.23]. Vitamin D levels were compared between Caucasian and African patients and it was concluded that Caucasian patients had a lower risk of vitamin D deficiency [RR 0.15, 95% CI (0.03 to 0.82; P = 0.03]. There was also an association between patients with idiopathic scoliosis and lower vitamin D -5.58, 95% CI [-7.10, -4.06]. Finally, no significant differences were observed in terms of curve magnitude assessed with the Cobb angle mean difference (MD) 4.45, 95% CI [-0.55, 9.44], or sex with lower-than-normal levels of vitamin D OR 0.96, 95% CI [0.58 to 1.60]. In conclusion, the incidence rates of vitamin D insufficiency and deficiency in patients with adolescent idiopathic scoliosis were 36.19% and 41.43%, respectively. The Caucasian race was associated with a lower risk of vitamin D deficiency compared to the African race. Vitamin D deficiency was not related to curve magnitude or sex.